2014
DOI: 10.1089/ars.2013.5406
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquinol-10 Supplementation Activates Mitochondria Functions to Decelerate Senescence in Senescence-Accelerated Mice

Abstract: Aim: The present study was conducted to define the relationship between the anti-aging effect of ubiquinol-10 supplementation and mitochondrial activation in senescence-accelerated mouse prone 1 (SAMP1) mice. Results: Here, we report that dietary supplementation with ubiquinol-10 prevents age-related decreases in the expression of sirtuin gene family members, which results in the activation of peroxisome proliferator-activated receptor c coactivator 1a (PGC-1a), a major factor that controls mitochondrial bioge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 73 publications
1
79
0
Order By: Relevance
“…Further study has illuminated the complex relationship between these transcription factors. Recent research on ubiquinol-10 has indicated that SIRT3 is under the control of cAMP/AMPK/SIRT1/PGC-1α signaling (Tian et al 2014), whereas SIRT5 is reported to increase ATP synthesis and oxygen consumption in HepG2 cells, which is antagonized by PGC-1α and AMPK (Buler et al 2014). Surprisingly, recent study suggests that the deacetylase SIRT6 can suppress hepatic glucose production by acting as a positive regulator of general control non-derepressible 5 (GCN5)-mediated acetylation of PGC-1α (Dominy et al 2012).…”
Section: Sirtuins (Sirts)mentioning
confidence: 99%
“…Further study has illuminated the complex relationship between these transcription factors. Recent research on ubiquinol-10 has indicated that SIRT3 is under the control of cAMP/AMPK/SIRT1/PGC-1α signaling (Tian et al 2014), whereas SIRT5 is reported to increase ATP synthesis and oxygen consumption in HepG2 cells, which is antagonized by PGC-1α and AMPK (Buler et al 2014). Surprisingly, recent study suggests that the deacetylase SIRT6 can suppress hepatic glucose production by acting as a positive regulator of general control non-derepressible 5 (GCN5)-mediated acetylation of PGC-1α (Dominy et al 2012).…”
Section: Sirtuins (Sirts)mentioning
confidence: 99%
“…Dietary supplementation with CoQ abolished age-related increases of SMPD activity in the rat liver plasma membrane [18]. Moreover, it was shown that a higher expression of muscle peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α), a major factor that controls mitochondrial biogenesis and respiration, protects from sarcopenia during aging [19] and that PGC-1α expression was increased in SAMP1 mice by dietary supplementation of reduced CoQ 10 (ubiquinol) [20]. …”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms responsible is an increase in the mass of skeletal muscle through protein synthesis. On the other hand, co-enzyme Q10 [11][12][13][14], L-carnitine [15,16], and polyphenol [17] have been reported as ingredients that effectively improve muscular metabolism and reduce oxidation stress.…”
Section: Backgroundsmentioning
confidence: 99%